Chemoprevention effect of the Mediterranean diet on colorectal cancer: Current studies and future prospects - Mahmod, Asma Ismail; Haif, Shatha Khaled; Kamal, Ayah; Al-ataby, Israa A.; Talib, Wamidh H. (Frontiers in Nutrition, 2022)
Colorectal cancer (CRC) is the third most common cancer and the second most deadly cancer worldwide. Nevertheless, more than 70% of CRC cases are resulted from sporadic tumorigenesis and are not inherited. Since adenoma-carcinoma development is a slow process and may take up to 20 years, diet-based chemoprevention could be an effective approach in sporadic CRC. The Mediterranean diet is an example of healthy diet patterns that consist of a combination of nutraceuticals that prevent several chronic diseases and cancer. Many epidemiological studies have shown the correlation between adherence to the Mediterranean diet and low incidence of CRC. The goal of this review is to shed the light on the anti-inflammatory and anti-colorectal cancer potentials of the natural bioactive compounds derived from the main foods in the Mediterranean diet.